Survival and malignant phenotype changes of human hepatoma SMMC-7721 cell line induced by cryopreservation at -50 °C - Jiang, Shi-Ming (World J Gastroenterol, 1997)
AIM: To investigate the effect of cryopreservation at -50 °C on the human hepatoma SMMC-7721 cell line. METHODS: With 15% DMSO as a cryoprotectant, the SMMC-7721 cells were cryopreserved at -50 °C, then thawed and recultured. The survival rate, mitotic index and LDH isoenzymes were compared between pre- and post-cryopreservation. RESULTS: Thirteen hours after the thaw, the mitotic index of cryopreserved SMMC-7721 cells decreased by 1.09%. The mode scope of chromosome number (46-53) after cryopreservation tended to transfer to that of normal human cells, and the percentage of metaphases containing 46 chromosomes changed from 0% to 16%. LDH isoenzymes changed from H-like model (LDH3(29.3%) > LDH4 (26.8%) > LDH2 (25.3%) > LDH5 (14.9%) > LDH1 (3.6%) to M-like model (LDH4 (48.3%) > LDH5 (28.3%) > LDH3 (18.9%) > LDH2 (4.4%) > LDH1 (0%)). This suggests that the survival rate could reach over 95%. CONCLUSION: Cryopreservation at -50 °C can be a convenient method for the cryopreservation of cell lines. However, cryopreservation at -50 °C is likely involved in the changes of the malignant phenotypes of the human hepatoma SMMC-7721 cell line, and may induce the differentiation of malignant cells.